Application of energy-saving hybrid distillation-pervaporation process for recycling organics from wastewater based on thermoeconomic and environmental analysis. (20th April 2021) - Wang, Shuai; Dai, Yao; Ma, Zhaoyuan; Qi, Huaqing; Chen, Zhengrun; Shen, Yuanyuan; Yang, Jingwei; Cui, Peizhe; Wang, Yinglong; Zhu, Zhaoyou; Gao, Jun
Abstract: Acetonitrile and n-propanol play an indispensable role in the manufacture of perfume and photosensitive materials, and the demand for these chemicals in China is growing. In this work, a series of processes was explored for achieving sustainable and green separation of wastewater containing acetonitrile and n-propanol. The solvent with high separation performance was determined by the combination of relative volatility and biological toxicity. Based on the sequential iterative optimization sequence and taking the minimum total annual costs (TAC) as the objective function, the program written by Visual Basic software was used to optimize the parameters of the basic process. The steam recompression assisted distillation and pervaporation (PV) technology are combined to reduce the energy consumption. Through the Heat Exchanger Network Synthesis (HENs) option, the heat recovery in the process was further improved. Furthermore, exergy and environmental analyses were further used to assess the feasibility of several separation processes. The results showed that compared to the basic process, the TAC and exergy loss of vapor recompression assisted distillation process were reduced by 43.6% and 12.65%, respectively. The use of heat integration and PV technology further reduced energy consumption. The TAC and emissions of novel hybrid process were saved by 74.6% and 53.87%, respectively, which indicates the feasibility of the processes for continuously updated cleaner production. Graphical abstract: Image 1 Highlights: A PV-distillation hybrid process is proposed to separate acetonitrile/n-propanol/water. Potential solvent is selected considering performance and toxicity. Visual Basic program is used to improve the process optimization efficiency. Economic, exergy and environmental analyses are adopted to evaluate the process feasibility.